Filter Cake as a Long-Standing Source of Micronutrients for Sugarcane - Crusciol, Carlos Alexandre Costa [UNESP]; McCray, James Mabry; de Campos, Murilo [UNESP]; do Nascimento, Carlos Antonio Costa; Rossato, Otávio Bagiotto; Adorna, Jaqueline Cristiane [UNESP]; Mellis, Estêvão Vicari (Springer Nature, 2021)
The aim of this study was to evaluate the residual effects of micronutrient application with or without filter cake on the supply of micronutrients, i.e., zinc (Zn), copper (Cu), manganese (Mn), iron (Fe), boron (B), and molybdenum (Mo), and sugarcane ratoon performance based on stalk and sugar yield. Two experiments were established in São Paulo state, Brazil, in a Rhodic Hapludox and a Typic Quartzipsamment in a randomized block design with an 8 × 2 factorial scheme. Seven micronutrient treatments (Zn, Cu, Mn, Fe, B, Mo, and all micronutrients) plus one control treatment combined with two filter cake rates (0 and 30 t ha−1) were applied in the planting furrow. Leaf micronutrient concentrations and stalk and sugar yields in the first, second, and third sugarcane ratoons were evaluated. The leaf concentrations of micronutrients were not affected by their application in the planting furrows but were affected by filter cake application. In addition, filter cake application increased stalk and sugar yields in both soil types and all ratoons. The micronutrients and filter cake applied in the planting furrow were able to supply micronutrients to sugarcane ratoons. The best plant response was attributed to B and Zn application, and a residual effect of filter cake application was observed in successive ratoons, with increased stalk and sugar yields.
Keywords: Leaf nutrient concentration; Residual effect; Saccharum spp; Stalk; Sugar